Hadith #3016 - Sunan Abi Dawud - Abdullah bin Muhammad al-Musandi عبد الله بن محمد المسندي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Jawayriyya bin Asma' bin 'Ubaid جويرية بن أسماء بن عبيد الضبعي; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
Abdullah ibn AbuBakr and some children of Muhammad ibn Maslamah said: There remained some people of Khaybar and they confined themselves to the fortresses. They asked the Messenger of Allah (ﷺ) to protect their lives and let them go. He did so. The people of Fadak heard this; they also adopted a similar way. (Fadak) was, therefore, exclusively reserved for the Messenger of Allah (ﷺ), for it was not captured by the expedition of cavalry and camelry.
Grade: Da'if

Hadith #3944 - Sunan Abi Dawud - Abdullah bin Muhammad bin Asma' عبد الله بن محمد بن أسماء; ibn Umar; Jawayriyya bin Asma' bin 'Ubaid جويرية بن أسماء بن عبيد الضبعي; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Ibn ‘Umar from the Prophet (ﷺ) to the same effect as mentioned by Ibrahim b. Musa through a different chain.
Grade: Da'if